The Sage deaf studies encyclopedia - Gertz, Genie; Boudreault, Patrick (Los Angeles : SAGE, 2016)
The time has come for a new in-depth encyclopedic collection of entries defining the current state of Deaf Studies at an international level using critical and intersectional lenses encompassing the field. The emergence of Deaf Studies programs at colleges and universities and the broadened knowledge of social sciences (including but not limited to Deaf History, Deaf Culture, Signed Languages, Deaf Bilingual Education, Deaf Art, and more) have served to expand the activities of research, teaching, analysis, and curriculum development. The field has experienced a major shift due to increasing awareness of Deaf Studies research since the mid-1960s. The field has been further influenced by the Deaf community's movement, resistance, activism and politics worldwide, as well as the impact of technological advances, such as in communications, with cell phones, computers, and other devices. This new Encyclopedia shifts focus away from the medical model that has viewed deaf individuals as needing to be remedied in order to correct so-called hearing and speaking deficiencies for the sole purpose of assimilation into mainstream society. The members of deaf communities are part of a distinct cultural and linguistic group with a unique, vibrant community and way of being. As precedence, The SAGE Deaf Studies Encyclopedia carves out a new and critical perspective that breathes meaning into organic deaf experiences through a new critical theory lens. Such a focus is novel in that it comes from deaf and hearing allies of the communities where historically, institutions of medicine and disability ride roughshod over authentic experiences.--Publisher website.
Volume 1. [A-D] -- Volume 2. [E-M] -- Volume 3. [N-Z].
"SAGE Reference."--title page.
Includes bibliographical references and index.
Keywords: Deaf people -- Study and teaching; Deaf people -- History -- Encyclopedias; Deaf culture -- Encyclopedias